2017
DOI: 10.21475/ajcs.17.11.07.pne552
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different rates of inorganic fertilizer on physiology, growth and yield of okra (Abelmoschus esculentus) cultivated on BRIS soil of Terengganu, Malaysia

Abstract: This study was designed to observe the effects of different application rates of inorganic fertilizers on growth, yield and quality of okra (Abelmoschus esculentus L. Moench) under BRIS soil condition. The field experiment was conducted during July, 2014 to April, 2015 at the teaching and research farm of University Sultan Zainal Abidin (UniSZA), Besut Campus, Terengganu. Performance of okra variety Singa 979 was assessed by application of NPK at different rates (0 kg ha -1 (control), 150 kg ha, 170 kg ha . Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 11 publications
3
15
1
Order By: Relevance
“…Besides, phosphorus stimulates cell division, elongation as well as flowering and fruit set. This finding was in conformity with the work of Khandaker et al, (2017) who reported that the highest number of branches (7) per plant recorded form the highest rate of NPK fertilizer rates. Depending on the cultivar used the environmental condition and soil factors the number of branches per plant completely different.…”
Section: Effect Of Nitrogen and Phosphorus Fertilizer Rates On Phenolsupporting
confidence: 92%
See 1 more Smart Citation
“…Besides, phosphorus stimulates cell division, elongation as well as flowering and fruit set. This finding was in conformity with the work of Khandaker et al, (2017) who reported that the highest number of branches (7) per plant recorded form the highest rate of NPK fertilizer rates. Depending on the cultivar used the environmental condition and soil factors the number of branches per plant completely different.…”
Section: Effect Of Nitrogen and Phosphorus Fertilizer Rates On Phenolsupporting
confidence: 92%
“…This may be higher doses of N and P fertilizer causes drop of leaf, drop of pod and reduce the quality of Okra pod. The result is in line with Khandaker et al (2017) who reported that Okra pod weight decreased with higher dose of NPK fertilizer. 3.2.4.…”
Section: Average Fruit Weightsupporting
confidence: 91%
“…This is supported by Edwards and Burrows 1988;Canellas et al 2002. Application of organic manures increases fresh weights of the fruits per plant (Khandaker et al, 2017). In a similar research conducted by Thriveni (2015), he reported that bitter gourd produces 4000 kg ha-1 of fruit weight with increased rate of vermicompost.…”
Section: Discussionmentioning
confidence: 81%
“…Results from this experiment shows that higher rate of vermicompost enhanced the stomatal conductance of watermelon crops. According to Khandaker et al (2017), the highest value of stomatal conductivity of chilli was recorded with the application of vermicompost. It was also observed from the results the higher the net photosynthetic rate the higher the stomatal conductance.…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, the weakest values were resulted with plants fertilized by 50% RDF. Khandaker et al (2017) on okra demonstrated that application of NPK shows the highest values regard chlorophyll content. Nasarudin et al (2018) found that the effect of NPK on the chlorophyll contents of rice was investigated with a view to the enhancement of high yield production.…”
Section: Leaves Pigment Contents (Mg/100g Fw)mentioning
confidence: 94%